2021
DOI: 10.31004/basicedu.v5i5.1399
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan E-Media Nearpod melalui Model Discovery untuk Meningkatkan Kemampuan Berpikir Kritis Siswa di Sekolah Dasar

Abstract: Menyadai pembelajaran belum efektif dan inovatif sehingga kemampuan berpikir kritis siswa masih rendah, dibutuhkan penelitian untuk meningkatkan rendahnya kemampuan berpikir kritis siswa. Penelitian pengembangan ini bertujuan menganalisis kelayakan dan efektivitas pengembangan E-Media Nearpod melalui Model Discovery untuk meningkatkan kemampuan berpikir kritis siswa kelas V sekolah dasar. Penelitian pengembangan ini bertujuan menganalisis kelayakan dan efektivitas pengembangan E-Media Nearpod melalui Model Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 8 publications
0
7
0
11
Order By: Relevance
“…With these limitations, the researcher suggests carrying out further development in various other subject matter and this can be done using software or other platforms so that students' understanding of the material can be further improved (Purnama & Pramudiani, 2021) Nearpod E-media can be concluded that the product developed in the form of Nearpod E-media after being validated by an expert validator obtains very feasible results so that it can be developed and used, therefore Nearpod E-media is an alternative media that can be used by teachers in learning eye content science lessons or other subject matter content. In addition, from the results of testing the effectiveness of product use, it can be concluded that Emedia Nearpod through the Discovery Model applied in learning can improve students' critical thinking skills so that this type of media can be declared effective (Susanto, 2021) This learning video media is so that learning in class runs smoothly and learning objectives can be achieved, so before using learning video media, the teacher should read the instruction manual for utilization. During learning the teacher acts as a facilitator who directs students when the learning process takes place.…”
Section: Discussionmentioning
confidence: 99%
“…With these limitations, the researcher suggests carrying out further development in various other subject matter and this can be done using software or other platforms so that students' understanding of the material can be further improved (Purnama & Pramudiani, 2021) Nearpod E-media can be concluded that the product developed in the form of Nearpod E-media after being validated by an expert validator obtains very feasible results so that it can be developed and used, therefore Nearpod E-media is an alternative media that can be used by teachers in learning eye content science lessons or other subject matter content. In addition, from the results of testing the effectiveness of product use, it can be concluded that Emedia Nearpod through the Discovery Model applied in learning can improve students' critical thinking skills so that this type of media can be declared effective (Susanto, 2021) This learning video media is so that learning in class runs smoothly and learning objectives can be achieved, so before using learning video media, the teacher should read the instruction manual for utilization. During learning the teacher acts as a facilitator who directs students when the learning process takes place.…”
Section: Discussionmentioning
confidence: 99%
“…Media pembelajaran nearpod juga bisa kita akses menggunakan website atau aplikasinya bisa juga kita unduh di laptop atau komputer. Nearpod juga menyajikan berbagai macam fitur untuk mempadukan dokumen presentasi, virtuallrealityy(VR), memasukkan PDF, dan lain-lain (Ami, 2021;Susanto, 2021). Dalam fitur aktivitas nearpod, aplikasi ini sudah dilengkapi kuis interaktif, memasukkan pertanyaan untuk jawaban panjang, tes memori, mengisi titik-titik, dan menjawab pertanyaan dengan gambar (Halloran, 2018;Widiyastuti et al, 2018).…”
Section: Pendahuluanunclassified
“…Menurut kajian dari (Arditya Isti et al, 2020), macam-macam media pembelajaran diklasifikasi menjadi empat bagian diantaranya: (1) media audio adalah media dalam bentuk penyajian suara seperti radio atau rekaman suara; (2) media visual merupakan media yang berhubungan dengan fungsi mata seperti menjabarkan berbagai gambar yang berkaitan dengan materi; (3) media audio-visual yaitu media yang menggabungkan antara unsur suara dan gambar dalam satu kesatuan; (4) dan multimedia yaitu media yang mengaitkan semua indera manusia seperti model tiga dimensi. Salah satu komponen media pembelajaran yang berbasis multimedia yaitu aplikasi Nearpod (Feri & Zulherman, 2021;Susanto, 2021;Xian, 2022;Abdullah et al, 2022).…”
Section: Pendahuluanunclassified
“…Media pembelajaran aplikasi Nearpod merupakan pilihan alat yang dapat digunakan oleh pendidik dalam pembelajaran muatan mata pelajaran IPA maupun muatan mata pelajaran lainnya (Susanto, 2021). Nearpod merupakan aplikasi belajar berbasis web yang melayani dan mengontrol interaksi selama pengaturan pengetahuan belajar (Hakami, 2020).…”
Section: Pendahuluanunclassified